Seedling morphology of four species of Ocimum L. (Lamiaceae) and its taxonomic significance (Bangladesh Journal of Plant Taxonomy, 2012)
Not available.DOI: http://dx.doi.org/10.3329/bjpt.v19i1.10946Bangladesh J. Plant Taxon. 19(1): 89-92, 2012 (June)